Avances de investigación. La no sujeción de las fundaciones al impuesto sobre la renta en Colombia : Visión desde el derecho español (2006)
This advance report presents the arguments of the Spanish doctrine that tends to agree with a total imposition of taxes on corporations (income tax in Colombia). The reasons could be summarized in four ideas: breaching of the equality principle for being a legal person; avoiding advantages that may distort the market; avoiding frauds; and finally, because they have payment power. Each of these ideas will be analyzed, contrasting them with Colombian reality.